(untitled) - Okumus, Fevzi (Oxford, U.K., 2010)
Strategic Management for Hospitality and Tourism is a vital text for all those studying cutting edge theories and views on strategic management. Unlike others textbooks in this area, it goes further than merely contextualizing strategic management for hospitality and tourism, and avoids using a prescriptive, or descriptive approach. It looks instead, at the latest in strategic thinking and theories, and provides critical and analytical discussion as to how and if these models and theories can be applied to the industry, within specific contexts such as culture, profit and non-profit organizations.
Keywords: Tourism,Strategic planning,Hoạch định chiến lược,Du lịch; Management,Quản lý